Co-operative Communication with Energy-Efficient in A Clustered Wireless Sensor Network - Bhagyashri V, Patil; Baviskar, PV (International Journal of Computer Sciences and Engineering, 2025)
The concept of co-operative communication is one of the fastest growing areas of research in wireless sensor networks. Energy efficiency is the main issue in the Wireless Sensor Networks (WSN). The energy consumption is minimized using cooperative communication technique. Number of techniques has been proposed in minimizing the energy consumption in wireless sensor networks. In this paper, the two techniques proposed for minimizing the energy consumption have been discussed. During the route discovery process AODV (Ad hoc On demand distance vector) floods the entire network with large number of control packets, and hence it finds many unused routes between the source and destination. This becomes a major drawback to AODV since this causes routing overhead, consuming bandwidth and node power. The proposed enhancement to AODV optimizes CAODV (Cluster Based AODV) by reducing the number of control messages generated during the route discovery process. The optimization method uses the idea of clustering the nodes of the network and managing routing by cluster heads and gateway nodes. Routing using clusters effectively reduces the control messaged flooded during the route discovery process by replacing broadcasting of RREQ packets with forwarding of RREQ packets to Cluster Heads. The performance evaluation of CAODV is carried out through simulation tests, which evince the effectiveness of this protocol in terms of network energy efficiency when compared against other well-known protocols.